Research on the Integration of Ideological and Political Education into Employment Education for College Students - Xu, Jiangfei (Education Insights, 2026)
College student employment is closely linked to public welfare and economic development, with job quality significantly impacting national talent strategies and global competitiveness. In the contemporary socio-economic landscape, many graduates face multifaceted challenges such as skewed employment perspectives, inadequate career planning, and profound social adaptation difficulties during their job search processes. These persistent issues not only hinder individual personal growth and professional trajectory but may also pose potential risks to broader social stability and economic productivity. Consequently, this study comprehensively examines the strategic integration of employment education with ideological and political education within higher education institutions. It systematically analyzes the critical role of combining practical employment training with robust ideological education, proposing concrete, actionable integration approaches tailored to modern academic environments. Furthermore, this research aims to guide students in establishing correct employment values, ethical perspectives, and a strong sense of social responsibility. The study focuses extensively on enhancing comprehensive competencies, cultivating core employability skills, and strengthening both ideological guidance and psychological resilience among graduates. By aligning these educational frameworks with overarching national strategic objectives and long-term talent development goals, this paper provides a sustainable model for universities. Ultimately, the proposed integrated educational paradigm seeks to empower college students to navigate the complex labor market successfully while contributing meaningfully to societal advancement and national prosperity.